Salicylic Acid-catalyzed Three-component Synthesis of 1-Amido/thioamidoalkyl-2-naphthols Under Solvent-free Conditions - Darbandi, Hassan; Kiyani, Hamzeh (Orbital: The Electronic Journal of Chemistry, 2019)
A simple, efficient, and green procedure for the solvent-free synthesis of 1-amido/thioamidoalkyl-2-naphthols by one-pot stirring of starting reactants at 100 °C has been introduced. By utilizing salicylic acid (SA) as the catalyst, the reaction of aryl aldehydes, 2-naphthol, and acetamide/benzamide/urea/thiourea were successfully performed, and 1-amido/thioamidoalkyl-2-naphthols were obtained in good to high isolated yields. The notable advantages of this method over some previous methods are the availability of catalyst, atom efficiency, not using any solvent for reaction, relatively green conditions, no need for catalyst synthesis, relatively shorter reaction times, and no specialized equipment (microwave or ultrasound) or purification techniques are needed. DOI: http://dx.doi.org/10.17807/orbital.v11i1.1355